An Example of Multidisciplinary Approach in the Medicolegal Evaluation of Cases Applying to the Forensic Medicine Polyclinic: Forensic Medicine and Radiology Joint Study Model - İzci, Abdülkadir; Acar, Kemalettin; Çakmak, Vefa; Arslanergül, Mesut; Kurtuluş Dereli, Ayşe (The Bulletin of Legal Medicine, 2025)
Objective: Evaluation of radiological images is frequently required in preparing a forensic report that requires multidisciplinary evaluation of cases. The aim of the councils that we organized with the joint participation of Forensic Medicine and Radiology was to emphasize the importance of multidisciplinary cooperation between the disciplines of forensic medicine and radiology for the professional and accurate evaluation of radiological findings and to present this approach as a model by considering the cases evaluated.Methods: Archive records between January 2019 and July 2022 were scanned, and the reports evaluated by our forensic medicine and radiology councils were evaluated in terms of age, gender, report type, pathologies evaluated in the council, and medicolegal results.Results: In our study, 266 cases were evaluated. It is seen that 57.1% (n=152) of the cases were trauma cases. Osseous pathologies constitute 54.9% (n=129) of the traumatic cases. The other 106 cases consisted of regional injuries and it was observed that thoracic (48.1%) and cranial pathologies (30.1%) were evaluated most frequently. In regional injuries, lung contusion and intracranial haemorrhages were frequently evaluated.Conclusion: We believe that evaluating radiological images affecting forensic medical evaluation together with forensic medicine and radiology specialists from a forensic medicine perspective and reaching a conclusion is important regarding forensic reporting and results. Therefore, we recommend the establishment of joint councils of the Forensic Medicine and Radiology Departments as a model to discuss cases that require the evaluation of a radiologist during the forensic medical evaluation process.
Keywords: forensic medicine; radiology; multidisciplinary